Mission-oriented R&D and growth - Thomas Ziesemer (Journal of Applied Economics, 2021)
We analyze the dynamic interaction of mission-oriented R&D expenditure stocks with domestic and foreign private and public R&D, total-factor-productivity (TFP), and gross domestic product (GDP) for seven EU countries. We use the vector-error-correction method. Permanent changes on mission-oriented R&D increase total-factor-productivity and GDP. On average across periods and countries, a 1% increase of mission-oriented R&D leads to an additional 0.485% public R&D, 0.705% private R&D, 0.485% for TFP, and 0.56% GDP. We also show years of positive gains, the sums of discounted net present values, and the average yearly gains/GDP ratio. Mission-oriented R&D has high internal rates of return.
Keywords: 330; cointegrating VAR; growth; mission-oriented R&D; Total factor productivity